Chemical reaction and radiation effects on unsteady MHD free convection flow in a porous medium past an infinite inclined isothermal plate - H. I., Osman; N. F. M., Omar; Vieru, D.; Zulkhibri, Ismail (Penerbit UMP, 2020)
The effect of chemical reaction on unsteady magentohydrodynamic (MHD) free convection flow in a porous medium past an infinite inclined plate has been investigated. Laplace transform technique is the method to solve the solutions for velocity, temperature and concentration fields. The analytical expressions for non-dimensional skin friction, Nusselt number and Sherwood number has been presented. The influence of various embedded parameter on velocity, temperature and concentration such as chemical reaction parameter, magnetic field and radiation has been discussed in detail. The effects of involved parameters have been discussed and the numerical results are presented graphically.